The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18632/oncotarget.13423
|View full text |Cite
|
Sign up to set email alerts
|

The impact of reproductive life on breast cancer risk in women with family history or BRCA mutation

Abstract: Reproductive history and exogenous hormonal exposures are acknowledged risk factors for breast cancer in the general population. In women at increased breast cancer risk for genetic predisposition or positive family history, data regarding these risk factors are limited or conflicting, and recommendations for these categories are unclear. We evaluated the characteristics of reproductive life in 2522 women at increased genetic or familial breast cancer risk attending our Family Cancer Center. Breast cancers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…This is supported by Lambertini et al study (17) which confirmed the protective effect of ever breastfeeding against hormone receptor-negative breast cancer, which is more common in younger women. Also, Toss et al (18) found a protective effect of breastfeeding only in triple negative breast cancer which represent only 15% of breast cancer cases and this explains the results of the present study which found that breastfeeding had no protective effect against familial breast cancer.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…This is supported by Lambertini et al study (17) which confirmed the protective effect of ever breastfeeding against hormone receptor-negative breast cancer, which is more common in younger women. Also, Toss et al (18) found a protective effect of breastfeeding only in triple negative breast cancer which represent only 15% of breast cancer cases and this explains the results of the present study which found that breastfeeding had no protective effect against familial breast cancer.…”
Section: Resultssupporting
confidence: 61%
“…The same finding was reported by results of several studies. (17,18,20) Horn et al (21) explained this finding by the fact that familial breast cancer is more frequently hormone receptor negative tumors, while age at menarche, age at first delivery and parity seems to modify mostly the incidence of hormone receptor-positive tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the availability of new biological drugs and a more rational use of therapies, the clinical outcome remains poor. Thus, the life expectancy of patients with advanced disease is dismal, and the median survival of a mixed population of metastatic breast cancer patients has not substantially improved in the last decades (Chia et al 2007, Dawood et al 2008, Welt et al 2016, Toss et al 2017.…”
Section: Probable Reasons For the Discrepancy Between Genetic And Biomentioning
confidence: 99%
“…Various factors play a role in breast cancer mutagenesis including gene mutations, prolonged endogenous and exogenous estrogen exposure, and family history. 32 Despite the advancements in cancer management, therapies that increase the survival rate while improving life quality of patients are still required. 33 As it avoids systemic adverse effects by exerting a local response and being capable of initiating antitumor immunity, PDT may be an attractive option for breast cancer treatment; both alone and in combination with other procedures.…”
Section: Resultsmentioning
confidence: 99%